2019
DOI: 10.1016/s1473-3099(19)30273-7
|View full text |Cite
|
Sign up to set email alerts
|

Extended-spectrum β-lactamase-producing Escherichia coli in human-derived and foodchain-derived samples from England, Wales, and Scotland: an epidemiological surveillance and typing study

Abstract: Background Extended-spectrum β-lactamase-producing Escherichia coli isolates (ESBL-E coli) cause more than 5000 cases of bacteraemias annually in the UK. The contribution of the food chain to these infections is debated. We aimed to identify the most important reservoirs of ESBL-E coli that colonise and infect humans to identify strategic intervention points.Methods Sampling for ESBL-E coli was done between Aug 1, 2013, and Dec 15, 2014. We used selective media to seek ESBL-E coli in routinely submitted sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
135
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(158 citation statements)
references
References 33 publications
15
135
3
5
Order By: Relevance
“…ST10 was the predominant MLST, and ST10 has been reported from clinical samples indicating the ST10 isolates can colonize in humans as well as animal (Wang et al, 2016). Recent study also found that ESBL-producing E. coli ST10 occurred in both humans and cattle, and CTX-M-14 was the predominant CTX-M type among the bovine isolates (Day et al, 2019). In the central area of Spain, ESBL-producing E. coli ST10 was disseminated carrying CTX-M-14 (Coque et al, 2008a), and another study showed that ST10 E. coli carried CTX-M-14, SHV-12, CTX-M-9, CTX-M-15, and CTX-M-32 (Oteo et al, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…ST10 was the predominant MLST, and ST10 has been reported from clinical samples indicating the ST10 isolates can colonize in humans as well as animal (Wang et al, 2016). Recent study also found that ESBL-producing E. coli ST10 occurred in both humans and cattle, and CTX-M-14 was the predominant CTX-M type among the bovine isolates (Day et al, 2019). In the central area of Spain, ESBL-producing E. coli ST10 was disseminated carrying CTX-M-14 (Coque et al, 2008a), and another study showed that ST10 E. coli carried CTX-M-14, SHV-12, CTX-M-9, CTX-M-15, and CTX-M-32 (Oteo et al, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…Other prevalent clonal groups (ST93, ST602, and ST2170) in domestic meat samples were isolated from chicken meat; these groups were isolated from chicken samples procured from different companies. Of these STs, ST93 and ST602 were reported to be infrequent in humans but more frequent in animal samples (specifically chicken) [24,76,77], suggesting that the strains of groups ST93 and ST602 were present in chicken, since farming stages and chicken act as reservoirs for these clonal groups. ST2170 was previously reported in retail chicken meat and turkey in Japan and Ecuador, respectively [68,78].…”
Section: Discussionmentioning
confidence: 99%
“…The widely-disseminated UTI-causing clones ST131, ST335 and ST10 were common among our E. coli strains and dominated our Kenyan collection. This is unsurprising as these ST's are reported to be circulating globally (Ben Zakour 2016; Sanjar et al 2015;Day et al 2019). What's remarkable is the detection .…”
Section: Discussionmentioning
confidence: 99%